Effect of rubber – silica filler interaction on the strength of filled vulcanizate / Norizah Abd. Karim - Abd. Karim, Norizah (2015)
Although the roles of rubber-filler interaction are understood and well documented, but issues on the rubber-filler interaction are still not entirely clear until today. There are two main issues here; what is the nature of the bond that produces the interaction? Is it physical or chemical in nature? And, what is the strength of this bond that introduces the rubber-filler interaction? With the passion to know further, this project was carried out to address those two issues. Coupling agent, bis[3-triethoxysilylpropyl-Jtetrasulfide abbreviated as TESPT, was added into the natural rubber compound with a view to enhance the rubber-silica interaction as a consequence of the poor interaction between silica and natural rubber chains due to different polarity between natural rubber and silica. Silica-filled rubber compounds were prepared by mixing SMR L with precipitated silica at constant loading i.e., 50 p.p.h.r. The amount of coupling agent was varied from 0,1,2,3,4,5 to 8 p.p.h.r. in order to study its influence on Young’s modulus and other physical properties. Apart from SMR L, Epoxidized Natural Rubber viz ENR 25 was also used so that the effect of polarity of ENR on silica filler can be investigated as well. Various mechanical tests were conducted to evaluate the effects of increasing levels of coupling agent towards physical strength of the vulcanizate. Simple extension test for both normal and swollen samples was conducted to determine the Young’s modulus. It was found that Young’s Modulus of the vulcanizate increased as the amount of coupling agent was increased for both SMR L and ENR 25 silica filled vulcanizate. The increase in the Young’s modulus was about 22% for NR and 32.5% for ENR25 at 8 pphr of TESPT relative to control sample (0 pphr TESPT). The trend (Young’s modulus increases with increasing TESPT) is similar for both normal and swollen samples respectively. The effect of pre-stressing on Young’s modulus was investigated with a view to evaluate the strength of the chemical bond at the rubber-filler interface. The Young’s modulus of silica-filled NR reduced by about 6% (at 0 TESPT) and 8.5% (8 pphr TESPT) after subjecting the samples to 2.14MPa of pre-stressing. The reduction in the Young’s modulus is more attributed to stress-softening rather than the breaking of chemical links at the rubber filler-interface. The results also show that the Young’s modulus of swollen samples (swollen in oil until equilibrium) decreased by about 38% (at 0 pphr TESPT) and 15% (at 8 pphr TESPT) relative to Young’s modulus of the control (0 pphr PST) of dry sample. This latter point indicates strongly that the interaction at the rubber-filler interface via TESPT is chemical in nature. Hysteresis tests were also conducted at 300% strain for six cycles for both swelling and non swelling samples to ascertain whether bonding at the silica filler-rubber interface via TESPT is chemical or physical in nature. The results also showed that, the amount of energy dissipated increased with increasing amount of TESPT for both swollen and dry samples respectively. Hence, it can be concluded that, silica fillers form a strong filler network (chemical linkage) when a coupling agent is introduced.